KEANEKARAGAMAN MAKROFUNGI DI KAWASAN TAMAN WISATA ALAM SUNGAI DUMAI - Lestari, Devi Putri Abda; Suwondo; Darmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Macrofungi are important components of forest ecosystems, functioning as decomposers, supporting biogeochemical cycles, and possessing potential as sources of food, medicine, and biological agents. The presence and distribution of macrofungi are strongly influenced by environmental conditions and the availability of suitable growth substrates. The Sungai Dumai Nature Tourism Park (Taman Wisata Alam/TWA Sungai Dumai) is a conservation area with diverse habitat types that potentially support macrofungal diversity; however, information regarding macrofungal diversity in this area remains limited. This study aimed to identify and describe the diversity of macrofungi found in the Sungai Dumai Nature Tourism Park. An exploratory method was employed using the cruise method and hand-sorting technique across three observation stations representing shaded, transitional, and open areas. The collected specimens were documented, identified based on their morphological characteristics, and analyzed descriptively. The results revealed a total of 30 macrofungal species belonging to 24 genera, 14 families, 7 orders, 3 classes, and 1 division. Station I recorded the highest number of species, with 12 species from 11 genera, followed by Station III with 10 species from 10 genera, and Station II with 8 species from 7 genera. Macrofungi were found growing on various substrates, particularly decaying wood, leaf litter, and soil. The most dominant group belonged to the order Polyporales. Environmental conditions at the study site, including temperature ranging from 22–24°C, humidity of 82–84%, soil pH of 6.3–6.8, light intensity of 885–1839 lux, and soil organic matter content of 1.30–3.20%, were within the optimal range for macrofungal growth. These findings indicate that the Sungai Dumai Nature Tourism Park possesses relatively high macrofungal diversity and has considerable potential as a source of biodiversity data and fungal ecological studies in the Riau region.